Integrated nitrogen management in rice (Oryza sativa) under system rice intensification - SARAVANAKUMAR, S (The Indian Journal of Agricultural Sciences, 2020)
Rice (Oryza sativa L.) is the most important food crop cultivated in India with the average productivity of 2.9 t/ha. Rice has the largest yield potential crop which is to be tapped with sound management technologies like appropriate nutrient management techniques along with adoption of system rice intensification. To sustain present food sufficiency and to meet future food requirements, India has to realize an annual growth rate of at least 3% in productivity of rice. To maintain the nutritional standards, fertilizer nutrients should be applied in balanced and required proportion. Among the different nutritional elements, nitrogen (N) has received prime attention both by the farmers and researchers. Relationship among the growth, yield and nitrogen utilization in rice are becoming increasingly understood at the physiological and molecular level. Moreover, time and method of nitrogen application play a crucial role in increasing efficiency of fertilizers as well as the productivity of rice. This review paper attempts to document the different sources of nitrogen and its effect on growth and productivity of rice under system rice intensification.